Rapid Separation and Determination of Five Phenolic Acids in Eucommia ulmoides Oliver by FASI-CZE - Huang, Wen-Yi; Wu, Mei-Yan; Li*, Li-Jun; Cheng, Hao; Hu, Da-Chun; Li, Yan-Qing (Asian Journal of Chemistry, 2014)
A new method for simultaneous separation and determination of five active phenolic acids (chlorgenic acid, vanillic acid, caffeic acid, gallic acid and protocatechuic acid) in Eucommia ulmoides oliver (EuO) by field-amplified sample injection-capillary zone electrophoresis (FASI-CZE) has been proposed. The determination conditions, which contain pH in background solution, concentration of Na2B4O7 and H3BO3, acetonitrile, injection time, injection voltage, separation voltage, were optimized. The operating buffer was composed of 40 mmol/L Na2B4O7, 40 mmol/L H3BO3 and 10 % (by volume) acetonitrile at pH 9.5 with a capillary of 50 μm i.d. × 55 cm (35 cm to the detector window). In addition, it worked under a constant temperature of 25 °C. The UV detection wavelength was 215 nm. The applied voltage was -10 kV, the separation voltage was 20 kV and the injection time was 480 s. The linear ranges of the method were 77.6-1241.6 μg/L for chlorgenic acid, 2.25-36 μg/L for vanillic acid, 9.8-156.8 μg/L for caffeic acid, 11.4-182.4 μg/L for gallic acid and 7.35-117.6 μg/L for protocatechuic acid. The recoveries were 95-104, 93-107, 94-110, 98-107 and 94-105 %, respectively. Besides, the RSDs of the peak area were less than 4 % and detection limits (S/N = 3) were 9.21, 0.097, 0.350, 0.304 and 0.118 μg/L for chlorgenic acid, vanillic acid, caffeic acid, gallic acid and protocatechuic acid, respectively.